2006
DOI: 10.1128/aac.00562-06
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Genetic Elements Carry the Tetracycline Resistance Gene tet (W) in the Animal Pathogen Arcanobacterium pyogenes

Abstract: The tet(W) gene is associated with tetracycline resistance in a wide range of bacterial species, including obligately anaerobic rumen bacteria and isolates from the human gut and oral mucosa. However, little is known about how this gene is disseminated and the types of genetic elements it is carried on. We examined tetracycline-resistant isolates of the animal commensal and opportunistic pathogen Arcanobacterium pyogenes, all of which carried tet(W), and identified three genetic elements designated ATE-1, ATE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 32 publications
2
28
0
1
Order By: Relevance
“…Structurally, these genes were 96 to 99% identical to the previously described tet(W) genes (3,6,14,18,29,32). The 657-bp upstream region in clone 10 was 99% identical to the corresponding regions in Arcanobacterium pyogenes strains OX9 and OX4 (DQ519394 and DQ517519) (6) (Fig. 1), while the similarity with the corresponding regions in six different genera of gut commensals was lower at 93 to 96% (14).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Structurally, these genes were 96 to 99% identical to the previously described tet(W) genes (3,6,14,18,29,32). The 657-bp upstream region in clone 10 was 99% identical to the corresponding regions in Arcanobacterium pyogenes strains OX9 and OX4 (DQ519394 and DQ517519) (6) (Fig. 1), while the similarity with the corresponding regions in six different genera of gut commensals was lower at 93 to 96% (14).…”
Section: Resultssupporting
confidence: 51%
“…In the present study we found two incidences of tet(W): clone 3 tet(W), which had higher identity with the genes described in reference 14), and clone 10 tet(W), which was more closely related to the genes described earlier (6). The flanking sequences of the tet(W) genes described here were different.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…To our knowledge, there are only six validated species within the genus Arcanobacterium (Ohba et al, 2007). Members of this genus have been isolated from both animal and human sources (Collins et al, 1982) and include the known pathogens Arcanobacterium pyogenes and Arcanobacterium haemolyticum, and the putative opportunistic pathogen Arcanobacterium bernardiae (Billington & Jost, 2006;Funke et al, 1995). Other species within the genus, such as Arcanobacterium phocae, are of unknown pathological significance (Hoyles et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The mosaic tet(W/N/W) gene characterized above was also initially reported in a mobilizable element called ATE-1 (35). A comparison of the original ATE-1 element of Trueperella (Arcanobacterium) pyogenes with insert IN-02 revealed extensive sequence homology upstream of tet(W/N/W), including the mob gene and the oriT region known to be essential for ATE-1 mobility (35), as well as a putative integrase (Fig.…”
Section: 5) the Name Tet(w/n/w) Was Assigned To This Gene Tet(w/nmentioning
confidence: 76%